A Case of Cerebral Vasculitis Associated with Ulcerative Colitis - Naveen Raj; Matthew Arkebauer; Barry Waters; Brucha Dickinson (Case Reports in Rheumatology)
Ulcerative colitis (UC) is a chronic, debilitating condition characterized by inflammation of the colonic mucosa. It is regarded as a systemic inflammatory disorder that can affect a number of organ systems. Central nervous system disease associated with UC is a rare sequela of inflammatory bowel disease, occurring in less than 5% of cases. These manifestations include arterial and venous thrombosis, leukoencephalitis, seizures, and vasculitis. We present a case of a 61-year-old female with a two-year history of well-controlled ulcerative colitis, who developed altered mental status and weakness. On brain imaging, she was found to have cerebral lesions which were biopsied. Histopathology subsequently revealed coagulative necrosis and inflammation characteristic of vasculitis. Rheumatology serologies were negative, and the patient was started on steroids that dramatically improved her neurological function, with no residual deficits, and led to resolution of the brain lesions.